2019
DOI: 10.1016/j.jqsrt.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiation transfer in cylindrical, toroidal and hemi-ellipsoidal plasmas

Abstract: We present solutions of the radiative transfer equation for cylinders, hollow hemi-ellipsoidal shells and tori for a uniform plasma of fixed geometry. The radiative transfer equation is explicitly solved for two directions of emission, parallel and perpendicular to the axis of symmetry. The ratio between the fluxes in these two directions is also calculated and its use in measuring the frequency resolved opacity of the plasma is discussed. We find that the optimal geometry to use this ratio as an opacity measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It was shown that two-dimensional radiative transfer simulations using the code Cretin 28 can reproduce the experimental line ratios to a much higher degree than models which do not include the plasma geometry. Additionally, it was found that the w/y ratio obtained from two different views of the cylinder can be used as a diagnostic of the ion density of the plasma 26,29 , given that these ratios are dictated by the optical depth of the plasma through the mean chord and the line of sight 18,19,30 , which is directly proportional to the ion density.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that two-dimensional radiative transfer simulations using the code Cretin 28 can reproduce the experimental line ratios to a much higher degree than models which do not include the plasma geometry. Additionally, it was found that the w/y ratio obtained from two different views of the cylinder can be used as a diagnostic of the ion density of the plasma 26,29 , given that these ratios are dictated by the optical depth of the plasma through the mean chord and the line of sight 18,19,30 , which is directly proportional to the ion density.…”
Section: Introductionmentioning
confidence: 99%
“…The content of Section 2.3 was published in its entirety in Journal of Quantitative Spectroscopy and Radiative Transfer[54], with the exception of the cylindrical case, which is an excerpt of a publication in High Energy Density Physics[55].…”
mentioning
confidence: 99%